ANALYZING THE DEVELOPMENT OF DIGITAL LITERACY FRAMEWORK IN EDUCATION: A SYSTEMATIC LITERATURE REVIEW - Imas Istiani; Eva Fatimah; Ahmad Husain; Anin Eka Sulistyawati; Sakina Sunmud; Yuvita Yuvita (Balai Besar Guru Penggerak Jawa Timur, 2023)
The development of technology massively increase during covid-19. Then, a dozen beneficial invention in many sectors such as education race to be better forward. This research aims to suggest and map the domains of digital literacy in each previous research without any reduction of meaning and analyze the development of digital literacy in education. This research used a systematic literature review as a method to find the result, meaning that the researcher has a procedure to collect the previous research. The procedure is for the researcher to collect 200 papers from Scopus Database, Search by “Digital Literacy” and filter by the keyword